Managing financial risks in International Business - Ponomarenko, Andrii; Taušer, Josef; Čajka, Radek, 1983-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The thesis investigates the techniques that firms engaged in international business use to manage different types of financial risks. These exposures affect firm's future cash flows. The analysis differentiate several financial risks, such as a foreign exchange risk, an interest rate risk, a country risk and a commodity price risk. Risk measurement and management are essential tasks of a firm's treasury department. Measurement methods, such as value-at-risk, regression analysis and sensitivity analysis are the most commonly used techniques to assess firm's exposure. Derivative contracts used in hedging strategies against financial risks inlcude forward and futures contracts, swaps and options. By means of case studies, the practical perspective of hedging against financial risks is examined and compared to theoretical approaches.
Vedoucí práce: Josef Taušer
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses